Electronic Beam Steering and Polarization Agile Planar Antennas in Liquid Crystal Technology - Karabey, Onur Hamza (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
This book describes the characterization of liquid crystal materials at microwave frequencies and the usage of these materials in reconfigurable planar antennas and in their electrical tunable components. It reports for the first time the realization of a two-dimensional electronic beam steering antenna and polarization agile planar antennas with liquid crystal display technology. It gives a detailed description of all the theoretical analyses, modeling and design methods that were involved in the realization of these devices as well as their validation using measurement of demonstrative prototypes.  This book also shows that low profile, low cost, high gain, electronic beam steering and polarization agile antennas can be fabricated in larger sizes by using existing automated liquid crystal display manufacturing techniques. The innovative ideas and method described in this work represent a considerable advancement in the field of electronically reconfigurable antennas based on liquid crystal technology and are expected to draw significant interest in the future. Such antennas may become important, for example, in mobile terminals integrated into the body of laptops (in the cover) or of automobiles (in the rooftop), ships or boats ,for which flat, low-profile and low-cost antennas are required.  .